DNA damage and repair in the female germline: contributions to ART. (12th December 2018) - Martin, Jacinta H; Aitken, R John; Bromfield, Elizabeth G; Nixon, Brett
Abstract: BACKGROUND: DNA integrity and stability are critical determinants of cell viability. This is especially true in the female germline, wherein DNA integrity underpins successful conception, embryonic development, pregnancy and the production of healthy offspring. However, DNA is not inert; rather, it is subject to assault from various environment factors resulting in chemical modification and/or strand breakage. If structural alterations result and are left unrepaired, they have the potential to cause mutations and propagate disease. In this regard, reduced genetic integrity of the female germline ranks among the leading causes of subfertility in humans. With an estimated 10% of couples in developed countries taking recourse to ART to achieve pregnancy, the need for ongoing research into the capacity of the oocyte to detect DNA damage and thereafter initiate cell cycle arrest, apoptosis or DNA repair is increasingly more pressing. OBJECTIVE AND RATIONALE: This review documents our current knowledge of the quality control mechanisms utilised by the female germline to prevent and remediate DNA damage during their development from primordial follicles through to the formation of preimplantation embryos. SEARCH METHODS: The PubMed database was searched using the keywords: primordial follicle, primary follicle, secondary follicle, tertiary follicle, germinal vesical, MI, MII oocyte, zygote, preimplantation embryo, DNA repair, double-strand break and DNA damage. These keywords were combined with other phrases relevant to the topic. Literature was restricted to peer-reviewed original articles in the English language (published 1979–2018) and references within these articles were also searched. OUTCOMES: In this review, we explore the quality control mechanisms utilised by the female germline to prevent, detect and remediate DNA damage. We follow the trajectory of development from the primordial follicle stage through to the preimplantation embryo, highlighting findings likely to have important implications for fertility management, age-related subfertility and premature ovarian failure. In addition, we survey the latest discoveries regarding DNA repair within the metaphase II (MII) oocyte and implicate maternal stores of endogenous DNA repair proteins and mRNA transcripts as a primary means by which they defend their genomic integrity. The collective evidence reviewed herein demonstrates that the MII oocyte can engage in the activation of major DNA damage repair pathway(s), therefore encouraging a reappraisal of the long-held paradigm that oocytes are largely refractory to DNA repair upon reaching this late stage of their development. It is also demonstrated that the zygote can exploit a number of protective strategies to mitigate the risk and/or effect the repair, of DNA damage sustained to either parental germline; affirming that DNA protection is largely a maternally driven trait but that some aspects of repair may rely on a collaborative effort between the male and female germlines. WIDER IMPLICATIONS: The present review highlights the vulnerability of the oocyte to DNA damage and presents a number of opportunities for research to bolster the stringency of the oocyte's endogenous defences, with implications extending to improved diagnostics and novel therapeutic applications to alleviate the burden of infertility.